The sandbag and the sunflower - Tan, Desmond Joon Liang (2015)
This is a scriptwriting project for a short film. This script is about a boxer, Ming, who is living a dull, monotonous and unfulfilling life. He meets a woman, Annie, who is tenant in his flat. Annie gets herself into trouble and it affects the life of Ming. Their relationship evolves from being strangers to forming a friendship, where they add colours and joy to the lives of each other. However, Ming is unable to express his appreciation towards Annie, as he feels uncomfortable with human interaction. One day, Annie goes missing. Ming discovers something about her and is unable to cope with it.